Nanoscale electronic devices and their applications - Shah, Khurshed Ahmad; Khanday, Farooq Ahmad (Boca Raton : CRC Press, 2020)
"This book help readers to acquire a thorough understanding of the fundamentals of solids at nanoscale besides their applications including operation and properties of recent nanoscale devices. The book includes seven chapters covering overview of electrons in solids, carbon nanotube devices and their applications, doping techniques, construction and operation details of channel Engineered MOSFETs, structural and operational details about the spin devices including applications. Structural and operational details of phase change memory (PCM), memristor and Resistive Random-access Memory (ReRAM) are also discussed. Besides, some applications of these phase change devices to logic design have also been presented"--
OCLC-licensed vendor bibliographic record.
Keywords: Nanoelectromechanical systems; SCIENCE / Physics; TECHNOLOGY / Electricity; TECHNOLOGY / Electronics / Microelectronics